Low-temperature wear-resistant castable prepared from waste high-voltage electric porcelain and preparation method of low-temperature wear-resistant castable

By using waste high-voltage electrical ceramics and ultra-high performance concrete design concepts, low-temperature wear-resistant castables are prepared, which solves the problem of difficulty in providing wear-resistant refractory materials in medium and low temperature environments in the prior art, and achieves the effect of efficient use of waste materials, reducing costs and broadening the application range.

CN119638454APending Publication Date: 2025-03-18YANGQUAN JINYU TONGDA HIGH TEMPERATURE MATERIALS +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411881470.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to provide materials that are both wear-resistant and refractory in low temperature environments, and the traditional high-temperature refractory materials have poor wear resistance at low temperatures and are costly, which limits their large-scale application.

Method used

Use waste high-voltage electric porcelain as raw material, combined with the ultra-high performance concrete design concept, and use the closest packing principle to prepare low-temperature wear-resistant castable materials, and use the high-temperature and hardness characteristics of waste high-voltage electric porcelain to improve the strength and durability of the material.

Benefits of technology

The wear resistance and fire resistance of the material are significantly improved in low temperature environments, the recycling of waste high-voltage electric porcelain is realized, the production cost is reduced, and the application scope of the material is broadened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of refractory materials, in particular to a low-temperature wear-resistant castable prepared from waste high-voltage electric porcelain and a preparation method of the low-temperature wear-resistant castable. The low-temperature wear-resistant castable prepared from the waste high-voltage electric porcelain comprises the following raw material components in percentage by weight: 50-54% of waste high-voltage electric porcelain aggregate, 10-15% of quartz sand, 10-16% of a binding agent, 3-5% of activated aluminum oxide micro powder, 3-5% of silicon micro powder, 4-7% of brown fused alumina powder and 3-5% of quartz powder. According to the invention, the design concepts of a high-temperature refractory material and low-temperature ultra-high performance concrete (UHPC) are integrated, the closest packing principle is adopted, solid waste high-voltage electric porcelain waste is used as aggregate particles, a reinforced matrix is formed, and a combination system is optimized; the low-temperature wear-resistant environment-friendly castable which achieves good integrity and use effect by means of self-combination of materials in a low-temperature environment (less than or equal to 300 DEG C) is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of refractory materials, and in particular to a low-temperature wear-resistant casting material prepared by using waste high-voltage electric porcelain and a preparation method thereof. Background Art

[0002] In many industrial production processes, such as coal transportation systems for thermal power generation, ore transportation and processing in mines, and primary processing of certain chemical raw materials, there are a large number of working conditions with temperatures below 300°C. In these low-temperature scenarios (200-300°C), equipment components must not only withstand the severe wear caused by continuous friction and impact of materials, but also have to have certain fire resistance to cope with occasional local high-temperature shocks or thermal stress changes.

[0003] However, conventional wear-resistant materials often find it difficult to take into account both refractory properties, while the wear resistance of traditional high-temperature refractory materials at low temperatures is unsatisfactory, and the high cost also limits its large-scale application. In addition, there are no wear-resistant refractory materials suitable for low-temperature working conditions (200-300°C) in the GB / T23294-2021 wear-resistant refractory material document. The existing low-temperature wear-resistant castables mostly use medium- and high-temperature wear-resistant castables, which are mainly wear-resistant refractory materials with corundum and silicon carbide as raw materials. They can only fully exert the wear resistance of the material itself under higher temperature conditions (greater than 1100°C), but are prone to severe wear problems under medium and low temperature conditions (below 800°C).

[0004] At the same time, with the development of the power system, the demand for insulating ceramics used in high-voltage systems has greatly increased, but the strict requirements on the performance of ceramics have caused the proportion of waste high-voltage ceramics in production to reach 5-25%, most of which are mainly landfilled, resulting in waste of land resources and environmental pollution. Currently, protecting the environment, saving resources, and improving the comprehensive utilization rate of resources are important issues facing various enterprises, so the recycling of waste high-voltage ceramics is particularly important.

[0005] Waste high-voltage porcelain has material properties such as high hardness, good chemical stability and high temperature resistance. Its main components are refractory components such as alumina. When waste high-voltage porcelain is used to prepare low-temperature wear-resistant refractory materials, the internal structure does not change during low-temperature solidification, and under low-temperature working conditions, the structure inside the waste high-voltage porcelain is not easily destroyed. Summary of the invention

[0006] The present invention provides a low-temperature wear-resistant castable prepared by using waste high-voltage insulators and a preparation method thereof. By using waste high-voltage insulators as raw materials, the design concepts of high-temperature refractory materials and low-temperature ultra-high performance concrete (UHPC) are integrated, and the principle of closest stacking is utilized to enable the strength of the low-temperature wear-resistant castable to be fully exerted in a low-temperature environment (200-300°C). At the same time, the waste high-voltage insulators can be recycled and the cost of the low-temperature wear-resistant castable can be reduced.

[0007] To achieve the above object, the present invention provides a low-temperature wear-resistant castable prepared by using waste high-voltage electric porcelain, comprising:

[0008] The raw material components and weight percentages are respectively 50-54% of solid waste high-voltage porcelain aggregate, 10-15% of quartz sand, 10-16% of binder, 3-5% of activated alumina powder, 3-5% of silicon powder, 4-7% of brown corundum powder and 3-5% of quartz powder.

[0009] Preferably, the waste high-voltage porcelain aggregate is crushed into particles, and then the particle size of the waste high-voltage porcelain aggregate is selected by screening to be in the range of 1 to 3 mm, the particle size of the quartz sand is selected to be in the range of 0 to 1 mm, and the average particle size of the silicon powder is less than 1 μm.

[0010] Preferably, the low-temperature wear-resistant castable prepared using waste high-voltage porcelain further comprises 0.1-0.5% of the total weight of the raw material components in the amount of a polycarboxylic acid water reducer, and 0.005-0.01% of the total weight of the raw material components in the amount of a retarder.

[0011] Preferably, half of the activated alumina fine powder has a particle size of less than 5 μm.

[0012] Preferably, the particle size of the brown corundum powder is 200 mesh, and the particle size of the quartz powder is 200 mesh.

[0013] Preferably, the low-temperature wear-resistant castable prepared by using waste high-voltage electric porcelain further comprises 6-6.5% water based on the total weight of the raw material components.

[0014] Preferably, the binder is silicate cement.

[0015] A method for preparing a low-temperature wear-resistant castable using waste high-voltage electric porcelain comprises the following specific steps:

[0016] S1. Crushing, screening and removing impurities from waste high-voltage electric porcelain to obtain waste high-voltage electric porcelain aggregate with a particle size of 1 to 3 mm;

[0017] S2. Take the waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the water, the polycarboxylate water reducer and the retarder according to weight ratio;

[0018] S3. The waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the polycarboxylate water reducer and the retarder are placed in a mixing box of a mixer;

[0019] S4. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0020] S5. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0021] S6. The molded castable is sent to a curing room at a temperature of 20 to 25°C and a relative humidity greater than 90% for curing for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0022] S7. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0023] S8. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0024] S9. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. After crushing the waste high-voltage porcelain, screen out high-voltage porcelain aggregates with a particle size less than 3mm, and adopt the ultra-high performance concrete (UHPC) design concept. By using ultra-fine particles and selected particles to achieve high packing density, the strength and durability of the material are significantly improved, and the gaps between the particles are smaller, which is conducive to improving the density and strength of the material.

[0027] 2. Using waste high-voltage porcelain as aggregate can help reduce the accumulation of solid waste and reduce the pressure on the environment, which is in line with the current concept of environmental protection and sustainable development. At the same time, waste high-voltage porcelain has material properties such as high hardness, good chemical stability, and high temperature resistance. Its main components are refractory components such as alumina. The prepared low-temperature refractory materials can make full use of their inherent properties. Using this low-cost material as aggregate can effectively reduce production costs and improve product competitiveness in the market while ensuring the basic performance of the castable.

[0028] 3. Through the test under the same low temperature working condition, it is found that the wear resistance of the low temperature wear-resistant castable using waste high voltage porcelain aggregate is better than the wear resistance of the high temperature wear-resistant castable in the prior art.

[0029] 4. The low-temperature curing characteristics (heat treatment at 200°C) make it suitable for some temperature-sensitive base materials or construction environments. For example, in some old equipment repair scenarios that cannot withstand high temperatures, low-temperature wear-resistant castables made of waste high-voltage ceramic aggregates can be constructed without damaging the original equipment structure, broadening the application range of castables. DETAILED DESCRIPTION

[0030] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0031] A low-temperature wear-resistant casting material prepared by using waste high-voltage electric porcelain, comprising:

[0032] The raw material components and weight percentages are as follows: solid waste high-voltage electric porcelain aggregate accounts for 50-54% of the total, quartz sand accounts for 10-15%, binder accounts for 10-16%, activated alumina powder accounts for 3-5%, silicon powder accounts for 3-5%, brown corundum powder accounts for 4-7%, and quartz powder accounts for 3-5%;

[0033] The waste high-voltage electric porcelain aggregate is crushed to form particles, and then the particle size of the waste high-voltage electric porcelain aggregate is selected by screening to be in the range of 1 to 3 mm, the particle size of the quartz sand is selected to be in the range of 0 to 1 mm, the average particle size of the silicon micropowder is less than 1 μm, the particle size of half of the activated alumina micropowder is less than 5 μm, the particle size of the brown corundum powder is 200 mesh, the particle size of the quartz powder is 200 mesh, and the binder is silicate cement;

[0034] Furthermore, the low-temperature wear-resistant castable prepared using waste high-voltage porcelain also includes 0.1-0.5% of the total weight of the raw material components in the form of a polycarboxylic acid water reducer, 0.005-0.01% of the total weight of the raw material components in the form of a retarder, and 6-6.5% of the total weight of the raw material components in the form of water.

[0035] A method for preparing a low-temperature wear-resistant castable using waste high-voltage electric porcelain comprises the following specific steps:

[0036] S1. Crushing, screening and removing impurities from waste high-voltage electric porcelain to obtain waste high-voltage electric porcelain aggregate with a particle size of 1 to 3 mm;

[0037] S2. Take the waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the water, the polycarboxylate water reducer and the retarder according to weight ratio;

[0038] S3. The waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the polycarboxylate water reducer and the retarder are placed in a mixing box of a mixer;

[0039] S4. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0040] S5. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0041] S6. The molded castable is sent to a curing room at a temperature of 20 to 25°C and a relative humidity greater than 90% for curing for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0042] S7. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0043] S8. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0044] S9. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0045] Example

[0046] In this embodiment, the raw material components of the low-temperature wear-resistant castable prepared from waste high-voltage porcelain are: 5.3 kg of waste high-voltage porcelain aggregate with a particle size of 1 to 3 mm, 1.4 kg of quartz sand, 1.5 kg of binder, 0.4 kg of activated alumina powder, 0.4 kg of silica powder, 0.6 kg of brown corundum powder, 0.4 kg of quartz powder; 0.03 kg of polycarboxylic acid water reducer and 0.00075 kg of retarder; and 0.6 kg of water.

[0047] The total weight of the raw material components in the embodiment is 10Kg. The above embodiment is prepared by the following steps to prepare the low-temperature wear-resistant castable prepared from waste high-voltage porcelain:

[0048] S1. Crushing, screening and removing impurities from waste high-voltage electric porcelain to obtain waste high-voltage electric porcelain aggregate with a particle size of 1 to 3 mm;

[0049] S2. Take the waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the water, the polycarboxylate water reducer and the retarder according to weight ratio;

[0050] S3. The waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the polycarboxylate water reducer and the retarder are placed in a mixing box of a mixer;

[0051] S4. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0052] S5. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0053] S6. The molded castable is sent to a curing room at a temperature of 20 to 25°C and a relative humidity greater than 90% for curing for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0054] S7. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0055] S8. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0056] S9. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0057] Comparative Example 1

[0058] In Comparative Example 1, the raw material components of the low-temperature wear-resistant castable prepared using brown corundum include 5.3Kg of brown corundum, 1.4Kg of quartz sand, 1.5Kg of binder, 0.4Kg of activated alumina powder, 0.4Kg of silicon powder, 0.6Kg of brown corundum powder, 0.4Kg of quartz powder, 0.03Kg of polycarboxylic acid water reducer, 0.00075Kg of retarder, and 0.55Kg of water.

[0059] The total weight of the raw material components in Comparative Example 1 is 10 Kg. The above Comparative Example 1 is prepared by the following steps:

[0060] S1. Weigh brown corundum, quartz sand, binder, activated alumina powder, silica powder, brown corundum powder, quartz powder, water, polycarboxylate water reducer and retarder according to weight ratio;

[0061] S2. Place brown corundum, quartz sand, binder, activated alumina powder, silica powder, brown corundum powder, quartz powder, polycarboxylate water reducer and retarder into the mixing box of the mixer;

[0062] S3. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0063] S4. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0064] S5. The molded castable is sent to a curing room at a temperature of 20 to 25 ° C and a relative humidity greater than 90% for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0065] S6. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0066] S7. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0067] S8. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0068] Comparative Example 2

[0069] In Comparative Example 2, the raw material components of the low-temperature wear-resistant castable prepared using waste high-voltage porcelain aggregates of different particle sizes include 2.0Kg of waste high-voltage porcelain aggregates with a particle size of 0-1mm, 1.3Kg of waste high-voltage porcelain aggregates with a particle size of 1-3mm, 1.6Kg of waste high-voltage porcelain aggregates with a particle size of 3-5mm, 1.8Kg of waste high-voltage porcelain aggregates with a particle size of 5-8mm, 1.5Kg of binder, 0.4Kg of activated alumina powder, 0.4Kg of silica powder, 0.6Kg of brown corundum powder, 0.4Kg of quartz powder, 0.03Kg of polycarboxylic acid water reducer and 0.00075Kg of retarder, and 0.68Kg of water.

[0070] The total weight of the raw material components in Comparative Example 2 is 10 Kg.

[0071] The above comparative example 2 is prepared by the following steps:

[0072] S1. Weigh waste high-voltage porcelain aggregate with a particle size of 0 to 1 mm, waste high-voltage porcelain aggregate with a particle size of 1 to 3 mm, waste high-voltage porcelain aggregate with a particle size of 3 to 5 mm, binder, activated alumina powder, silica powder, brown corundum powder, quartz powder, water, polycarboxylate water reducer and retarder according to weight ratio;

[0073] S2. Place high-voltage porcelain aggregates of different particle sizes, binders, activated alumina powder, silica powder, brown corundum powder, quartz powder, polycarboxylate water reducer and retarder into the mixing box of the mixer;

[0074] S3. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0075] S4. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0076] S5. The molded castable is sent to a curing room at a temperature of 20 to 25 ° C and a relative humidity greater than 90% for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0077] S6. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0078] S7. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0079] S8. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0080] Comparative Example 3

[0081] In Comparative Example 3, the raw material components of the low-temperature wear-resistant castable prepared using waste high-voltage porcelain aggregates and 97 silicon carbide of different particle sizes include 1.6Kg of waste high-voltage porcelain aggregates with a particle size of 0-1mm, 0.8Kg of waste high-voltage porcelain aggregates with a particle size of 1-3mm, 1.6Kg of waste high-voltage porcelain aggregates with a particle size of 3-5mm, 1.8Kg of waste high-voltage porcelain aggregates with a particle size of 5-8mm, 0.5Kg of 97 silicon carbide with a particle size of 1-3mm, 0.4Kg of 97 silicon carbide with a particle size of 0-1mm, 1.5Kg of binder, 0.4Kg of activated alumina powder, 0.4Kg of silicon powder, 0.6Kg of brown corundum powder, 0.4Kg of quartz powder; 0.03Kg of polycarboxylic acid water reducer and 0.00075Kg of retarder; and 0.63Kg of water.

[0082] The total weight of the raw material components in Comparative Example 3 is 10 Kg.

[0083] The above comparative example 3 is prepared by the following steps:

[0084] S1. Weigh by weight waste high-voltage porcelain aggregate with a particle size of 0 to 1 mm, waste high-voltage porcelain aggregate with a particle size of 1 to 3 mm, waste high-voltage porcelain aggregate with a particle size of 3 to 5 mm, waste high-voltage porcelain aggregate with a particle size of 5 to 8 mm, 97 silicon carbide with a particle size of 1 to 3 mm, 97 silicon carbide with a particle size of 0 to 1 mm, binder, activated alumina powder, silicon powder, brown corundum powder, quartz powder, water, polycarboxylic acid water reducer and retarder;

[0085] S2. High-voltage porcelain aggregates of different particle sizes, 97 silicon carbide of different particle sizes, binders, activated alumina powder, silica powder, brown corundum powder, quartz powder, polycarboxylate water reducer and retarder are placed in the mixing box of the mixer;

[0086] S3. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0087] S4. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0088] S5. The molded castable is sent to a curing room at a temperature of 20 to 25 ° C and a relative humidity greater than 90% for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days;

[0089] S6. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0090] S7. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h;

[0091] S8. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0092] Comparative Example 4

[0093] In Comparative Example 4, the raw material components of the low-temperature wear-resistant castable prepared from waste high-voltage porcelain are: 5.3 kg of waste high-voltage porcelain aggregate with a particle size of 1 to 3 mm, 1.4 kg of quartz sand, 1.5 kg of binder, 0.4 kg of activated alumina powder, 0.4 kg of silica powder, 0.6 kg of brown corundum powder, 0.4 kg of quartz powder, 0.03 kg of polyethylene glycol-based polymer high-efficiency water reducer and 0.00075 kg of retarder, and 0.6 kg of water.

[0094] The total weight of the raw material components in Comparative Example 4 is 10 Kg, and the binder is aluminate cement.

[0095] The above comparative example 4 is prepared by the following steps using waste high voltage porcelain to prepare a low temperature wear-resistant castable:

[0096] S1. Crushing, screening and removing impurities from waste high-voltage electric porcelain to obtain waste high-voltage electric porcelain aggregate with a particle size of 1 to 3 mm;

[0097] S1. Take waste high-voltage porcelain aggregate with a particle size of 1 to 3 mm, quartz sand, binder, activated alumina powder, silica powder, brown corundum powder, quartz powder, water, polyethylene glycol high-efficiency water reducer and the retarder according to weight ratio;

[0098] S2. Place waste high-voltage porcelain aggregate, quartz sand, binder, activated alumina powder, silica powder, brown corundum powder, quartz powder, polyethylene glycol high-efficiency water reducer and retarder into the mixing box of the mixer;

[0099] S3. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min;

[0100] S4. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding;

[0101] S5. The molded castable is sent to a curing room at a temperature of 20 to 25 ° C and a relative humidity greater than 90% for 24 hours, and then demolded and continued to be cured in the air for 1 to 2 days;

[0102] S6. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours;

[0103] S7. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 1200°C and continued for 3 hours;

[0104] S8. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.

[0105] It should be noted that the molding process in Example, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 adopts vibration molding, with a vibration frequency of 30-50 Hz, an amplitude of 0.5-1 mm, and a vibration time of 1-2 minutes, so that the castable is molded.

[0106] Furthermore, the water reducers in Example, Comparative Example 1, Comparative Example 2 and Comparative Example 3 use polycarboxylate water reducers, while Comparative Example 4 uses polyethylene glycol high-efficiency water reducers.

[0107] It should be noted that Comparative Example 1 is a formula used in the prior art, wherein the raw material component in Comparative Example 1 adopts brown corundum with high cost and high hardness.

[0108] The differences between the remaining embodiments, comparative example 2, comparative example 3 and comparative example 4 are as follows: the raw material components in the embodiments are waste high-voltage porcelain aggregates and quartz sand with a particle size of 1 to 3 mm, the raw materials in comparative example 2 are waste high-voltage porcelain aggregates with a variety of different particle sizes, the raw materials in comparative example 3 are waste high-voltage porcelain with different particle sizes and 97 silicon carbide with high wear resistance and different particle sizes, the silicate cement binder in the embodiment is replaced by a high-temperature aluminate cement binder in comparative example 4, and a polyethylene glycol polymer high-efficiency water reducer is used which is different from the polycarboxylic acid water reducer.

[0109] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the low-temperature wear-resistant castable prepared by using waste high-voltage electric porcelain in the examples and the low-temperature wear-resistant castable prepared by using brown corundum in the comparative examples as follows:

[0110] Physical property testing: the bulk density of the low-temperature wear-resistant castable prepared using waste high-voltage porcelain in the example and the low-temperature wear-resistant castable prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 was measured according to GB / T2997-2015 "Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products".

[0111] For the room temperature compressive strength test, the low-temperature wear-resistant castable prepared by using waste high-voltage porcelain in the embodiment and the low-temperature wear-resistant castable prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are placed in a pressure testing machine and tested in accordance with GB / T5072-2008 "Test method for room temperature compressive strength of refractory materials". The loading rate is 0.5 MPa / s until the sample is destroyed, the maximum pressure value is recorded and the room temperature compressive strength is calculated.

[0112] For wear resistance test, the low-temperature wear-resistant castable prepared by using waste high-voltage porcelain in the example and the low-temperature wear-resistant castable prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested according to GB / T18301-2012 "Test method for wear resistance of refractory materials at room temperature". 1000g of silicon carbide sand with a specified particle size grade was vertically sprayed through a sandblasting tube using 450kPa compressed air to the flat surface of the sample, and the wear volume of the sample was measured.

[0113] The Archimedean drainage method is used below to test the bulk density of Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4. The test results are shown in the following table:

[0114]

[0115] It can be seen that the bulk density of the embodiment, comparative example 1, comparative example 2, comparative example 3 and comparative example 4 is 2.4-3.0 g / cm 3 Therefore, Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 all have higher density.

[0116] The following is a room temperature compressive strength test of Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 after drying at 110°C for 24 hours and heat treatment at 200°C for 3 hours. The test results are shown in the following table:

[0117]

[0118] The above test results show that the low-temperature wear-resistant castables prepared by Comparative Example 2, Comparative Example 3, Comparative Example 4 and the embodiment from the aspects of raw material composition, particle gradation and binder all meet the strength requirements of existing use;

[0119] At the same time, the data in the above table show that the room temperature compressive strength of the low temperature wear-resistant castable prepared in Example is closest to the room temperature compressive strength of the low temperature wear-resistant castable prepared in Comparative Example 1, so the performance of Example is closest to the performance of Comparative Example 1.

[0120] The following is a room temperature flexural strength test of the embodiment and the comparative example after drying at 110°C for 24 hours and heat treatment at 200°C for 3 hours. The test results are shown in the following table:

[0121]

[0122] The above test results show that the low-temperature wear-resistant castables prepared by Comparative Example 2, Comparative Example 3, Comparative Example 4 and the embodiment from the aspects of raw material composition, particle gradation and binder all meet the strength requirements of existing use;

[0123] At the same time, the data in the above table show that the room-temperature flexural strength is from high to low in the following order: Comparative Example 1 > Example > Comparative Example 3 > Comparative Example 2 > Comparative Example 4. The room-temperature flexural strength of the example is higher than that of Comparative Example 2, Comparative Example 3 and Comparative Example 4. At the same time, the room-temperature flexural strength of the example is close to that of Comparative Example 1. Therefore, the performance of the example is closest to that of Comparative Example 1.

[0124] The wear volume test of the embodiment and the comparative example after drying at 110°C for 24 hours and heat treatment at 200°C for 3 hours in a 200°C environment was carried out for 3 hours. The test results are as follows:

[0125]

[0126] The above test results show that the wear volumes at room temperature are as follows from high to low: Comparative Example 1, Example, Comparative Example 3, Comparative Example 2 and Comparative Example 4, wherein the larger the wear volume, the worse the wear resistance.

[0127] It can be seen from the above table that the raw materials in Comparative Example 2 cannot improve the overall wear resistance of the castable by adding waste high-voltage porcelain aggregates of different particle sizes. The raw material components in Comparative Example 3 adopt the waste high-voltage porcelain aggregates of different particle sizes in Comparative Example 2 and add highly wear-resistant 97 silicon carbide. Although its actual wear resistance test effect is greater than the wear resistance of Comparative Example 2, it is still less than the wear resistance of the embodiment. The raw material components of Comparative Example 4 are the same as those of the embodiment except for the binder component, but the wear resistance in the actual low-temperature environment is the worst.

[0128] Therefore, the wear resistance of the embodiment is closer to the wear resistance of the comparative example 1, and the performance of the embodiment is closest to the performance of the comparative example 1.

[0129] It should be noted that the maximum operating temperature of the comparative example and the embodiment needs to be tested, and the test results are as follows:

[0130]

[0131] The above test results show that Comparative Example 1, Comparative Example 2, Comparative Example 3 and the embodiment are all heat treated in a low temperature environment (200-300°C), while Comparative Example 4 needs to be heat treated in a medium to high temperature environment, so that Comparative Example 1, Comparative Example 2, Comparative Example 3 and the embodiment do not require excessively high temperatures for curing during the preparation process, thereby reducing energy consumption in the production process and thereby reducing energy costs.

[0132] Based on all the above test results, the performance values ​​of the low-temperature wear-resistant castables prepared in Example, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 in various index tests are obtained.

[0133] It is found that the room temperature compressive strength, room temperature flexural strength and wear resistance of the embodiment are close to those of comparative example 1, while the wear resistance of comparative examples 2, 3 and 4 is lower than that of the embodiment.

[0134] Among them, the microstructure and chemical composition of the waste high-voltage porcelain itself in the embodiment have good wear resistance. At the same time, the waste high-voltage porcelain material usually has a higher hardness and a dense structure. When it is distributed as an aggregate in the low-temperature wear-resistant castable of this embodiment, it can effectively resist external friction and wear and enhance the overall wear resistance of the low-temperature wear-resistant castable.

[0135] It should be noted that the cost of the waste high-voltage porcelain in the raw material components of the embodiment is less than the cost of the brown corundum in the comparative example 1. Therefore, the embodiment of the present invention has more advantages in use effect and cost control in a low temperature environment (200-300°C).

[0136] In the embodiment of the present invention, the waste high-voltage electric porcelain in the raw material component has material properties such as high hardness, good chemical stability, and high temperature resistance. Its main component is refractory components such as alumina. The advantage of using waste high-voltage electric porcelain to prepare low-temperature wear-resistant refractory materials is that it can make full use of its inherent properties, reduce dependence on new resources, reduce waste treatment costs and environmental pressure, and effectively reduce energy consumption under low-temperature preparation conditions. The prepared material has excellent wear resistance and can be widely used in industrial kilns and other scenes that require wear resistance and fire resistance, thereby achieving efficient recycling and sustainable development of resources.

[0137] In the embodiment of the present invention, the quartz sand in the raw material components is fine aggregate. Quartz sand mainly plays a filling role in cement (ultra-high performance concrete). Quartz sand can fill the gaps between particles of cement, mineral admixtures, etc., reduce the porosity in the concrete formed by the cement hydration reaction, and make the concrete structure denser. At the same time, quartz sand can serve as the skeleton of concrete and bear part of the load. When the concrete is subjected to pressure or tension, the fine aggregate particles transfer stress through the bonding of the cementitious material (cement) and jointly resist the external force with the cement paste. The hardness and strength characteristics of the fine aggregate will also affect the wear resistance and erosion resistance of the ultra-high performance concrete.

[0138] In the embodiment of the present invention, the silicon micropowder in the raw material components is a mineral admixture, wherein the particles of the silicon micropowder are very fine, and the average particle size is about 1 / 100 of the cement particles, and can be filled in the gaps between the cement particles. At the same time, the active silicon dioxide (SiO2) in the silicon micropowder will undergo a secondary hydration reaction with the calcium hydroxide (Ca(OH)2) produced by the hydration of cement to generate more CSH gel, further improving the microstructure of the concrete, and improving the density and strength of the concrete. The spherical particles of the silicon micropowder can play a "ball" effect, reducing the friction between the particles inside the concrete, making the concrete smoother during mixing, transportation and pouring. Finally, the addition of mineral admixtures can reduce the amount of cement used, thereby reducing the generation of hydration heat and avoiding temperature cracks caused by excessive internal temperature of the concrete.

[0139] In an embodiment of the present invention, the silicate cement in the raw material components is the main cementitious material of ultra-high performance concrete. After adding water, the mineral components on the surface of cement particles will undergo hydration reaction to generate hydration products such as hydrated calcium silicate (CSH) gel and calcium hydroxide. These hydration products bond other solid particles together to form a solid overall structure, wherein the hydration products generated by cement hydration are one of the important sources of concrete strength, along with the progress of hydration reaction, hydrated calcium silicate gel is continuously filled in the pores of concrete, the porosity of concrete is reduced, and the structure is more compact, thereby improving the strength indexes such as compression resistance and flexural resistance of concrete, and for ultra-high performance concrete, high-strength grade cement helps to achieve its ultra-high strength performance, so that it can withstand huge pressure and tension.

[0140] In the embodiment of the present invention, a polycarboxylate water-reducing agent is used. The polycarboxylate water-reducing agent can be adsorbed on the surface of cement particles, so that the cement particles carry the same charge, thereby generating electrostatic repulsion, so that the cement particles are dispersed more evenly in water. At the same time, the water-reducing agent can also reduce the surface tension between the cement particles and water, release more free water, and reduce the water consumption of concrete while maintaining the workability of concrete. For example, the polycarboxylate-based high-efficiency water-reducing agent can make ultra-high performance concrete still have good fluidity at a lower water-cement ratio, which is conducive to achieving ultra-high strength of concrete.

[0141] In summary, the present invention forms a stable skeleton structure in the system by precisely controlling the types and particle size distribution of the raw material components, thereby providing high temperature resistance for the whole. At the same time, the cementitious materials, active and inactive admixtures in the ultra-high performance concrete components interact with each other to fill the gaps in the skeleton and enhance the binding force, optimize the distribution of hydration products to improve the density, and cooperate with the admixtures of water reducers and flocculants to adjust the fluidity and setting time, so as to meet the wear resistance, impact resistance and overall structural stability in low temperature environments, thereby meeting the stringent requirements of relevant industrial scenarios for low-temperature wear-resistant castables.

[0142] In addition, the low-temperature (≤300°C) wear-resistant castable prepared by the present invention using waste high-voltage porcelain has significant advantages. In terms of particle grading, after reasonable allocation, its internal structure is more compact and stable, which is conducive to improving the overall performance; from the perspective of raw material resource utilization, it realizes the effective reuse of waste high-voltage porcelain, which not only reduces resource waste but also conforms to the concept of environmental protection; its applicable temperature range is less than 300°C, which can well meet the corresponding low-temperature working conditions; in terms of cost, with the help of waste resources as raw materials, the production cost is effectively reduced; in terms of performance, it has excellent wear resistance and can work stably for a long time in a low-temperature environment. For example, the national standard GB / T23294-2021 "Wear-resistant Refractory Materials" stipulates the wear volume of wear-resistant refractory materials for circulating fluidized bed boilers, urban domestic waste incinerators, industrial waste incinerators, medical waste incinerators, ordinary solid waste incinerators, hazardous waste incinerators and petroleum catalytic cracking devices. Most of them are limited to the wear volume after heat treatment at 815°C×3h and 1000°C×3h, and its wear volume is ≤6.0cm 3 The national standard GB / T23294-2021 "Wear-resistant Refractory Materials" does not specify the wear volume at low temperature (≤300°C), while the low-temperature wear-resistant castable prepared by the present invention only needs to be heat treated at 200°C, and its wear volume is less than 4.5cm 3, , thus making the wear resistance better.

[0143] In the description of the present invention, it is necessary to understand that the terms “longitudinal”, “lateral”, “length”, “width”, “thickness”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside” and “outside” orientations or positional relationships are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0144] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. A low-temperature wear-resistant castable prepared from waste high-voltage porcelain, characterized in that ,include: The raw material components and weight percentages are respectively 50-54% of solid waste high-voltage electromagnetic aggregate, 10-15% of quartz sand, 10-16% of binder, 3-5% of activated alumina powder, 3-5% of silicon powder, 4-7% of brown corundum powder and 3-5% of quartz powder.

2. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 1, characterized in that: The waste high-voltage porcelain aggregate is crushed into particles, and then the particle size of the waste high-voltage porcelain aggregate is selected by screening to be in the range of 1 to 3 mm, the particle size of the quartz sand is selected to be in the range of 0 to 1 mm, and the average particle size of the silicon powder is less than 1 μm.

3. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 1, characterized in that: The invention also comprises 0.1-0.5% of the total weight of the raw material components in the amount of a polycarboxylate water reducer and 0.005-0.01% of the total weight of the raw material components in the amount of a retarder.

4. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 1, characterized in that: Half of the activated alumina fine powder has a particle size of less than 5 μm.

5. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 1, characterized in that: The particle size of the brown corundum powder is 200 mesh, and the particle size of the quartz powder is 200 mesh.

6. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 3, characterized in that: The raw material components also include 6-6.5% water by weight.

7. The low-temperature wear-resistant castable prepared from waste high-voltage porcelain according to claim 1, characterized in that: The binder is silicate cement.

8. A method for preparing a low-temperature wear-resistant castable using waste high-voltage electric porcelain as claimed in claim 6, characterized in that: The specific steps include: S1. Crushing, screening and removing impurities from waste high-voltage electric porcelain to obtain waste high-voltage electric porcelain aggregate with a particle size of 1 to 3 mm; S2. Take the waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the water, the polycarboxylate water reducer and the retarder according to weight ratio; S3. The waste high-voltage porcelain aggregate, the quartz sand, the binder, the activated alumina powder, the silica powder, the brown corundum powder, the quartz powder, the polycarboxylate water reducer and the retarder are placed in a mixing box of a mixer; S4. After 1 min of pre-mixing, add 80% of the total water, continue to stir and mix for 5 min, and then add the remaining water according to the stirring condition in the mixing box, so that the raw materials are fully stirred into a putty-like state. The stirring time during this stirring process shall not be less than 10 min; S5. Pour the stirred castable into a pre-prepared mold and form the castable by vibration molding or static pressure molding; S6. The molded castable is sent to a curing room at a temperature of 20 to 25°C and a relative humidity greater than 90% for curing for 24 hours, and then demolded and continued to be cured in the air for 3 to 5 days; S7. The castable cured in air is sent to a drying room for drying at a temperature of 110°C and continued for 24 hours; S8. The dried castable is sent to a heat treatment chamber for heat treatment at a temperature of 200°C and continued for 3h; S9. Send the heat-treated castable material into a static chamber to allow the castable material to stand and cool.